Study on Niosh model of job stress: Relationship between role demands, management styles, interpersonal relationship and stress at Pos Logistics Berhad / Nurul Ain Anisha Abdul Hadi - Abdul Hadi, Nurul Ain Anisha (2019)
Purpose of study is to identify the relationship between role demands, management style and interpersonal relationship at Pos Logistics Berhad, Shah Alam. Correlation research methodology has been adapted in this study to response on research objective. The study used simple random sampling technique which took place at Pos Logistics Berhad, Shah Alam that involving 110 respondents for 8 departments. In order to make understanding to respondents, the questionnaires used translation between Malay and English and used “likert scale” were distributed. From the questionnaire, the data gained then analysed using IBM Statistical Package for the Social Science (SPSS) version 2.0 software. Based on SPSS software, the result can show which is survey rate, demographic statistic, reliability analysis, normality test, mean, and Pearson Coeffient. The outcome of the research showed that there is a relationship between role demands, management style and interpersonal relationship and stress at Pos Logistics Berhad, Shah Alam. Meanwhile the most contributing variable factors and stress which is role demands and the least contributing variable and stress is interpersonal relationship